The use of photovoice with people with intellectual disabilities: reflections, challenges and opportunities - Povee, Kate; Bishop, Brian John; Roberts, Lynne (Routledge, 2014)
Photovoice is part of the growing use of participatory research approaches with people with intellectual disabilities. In this paper we explore the process, opportunities and challenges associated with the use of photovoice with people with intellectual disabilities, illustrated through a research project entitled ‘This Is Me’. Photovoice requires researchers to share power and control in the research process and to tolerate uncertainty. Large investments in time and money are also required. These challenges, however, are outweighed by the benefits of the use of photovoice with people with intellectual disabilities. Photovoice creates a space where people with intellectual disabilities can meaningfully participate and exert control in the research process, and as such is an empowering experience. As a participatory research approach, photovoice is accessible and offers the opportunity for people with intellectual disabilities to develop new skills, confidence and experience inclusiveness in their own terms.